Perforated Meckel's diverticulum in neonates: a report of six cases and systematic review of the literature - Naeem Liaqat; Anies Mahomed; Sajid Iqbal Nayyar; Nadeem Akhtar; Sajjad Ali; Naveed Haider (SpringerOpen, 2022)
Abstract Background Perforation of Meckel Diverticulum (MD) is a rare cause of pneumoperitoneum in neonates. We hereby report six cases of perforation of MD in neonates, with addition of 53 cases from systematic review of the literature. A systematic review was performed using Mesh terms "Neonate, Meckel Diverticulum, Perforation, Pneumoperitoneum." All reports of perforated MD in the English literature were identified. Details of our 6 cases were analyzed in similar fashion. Results A total of 3027 manuscripts were screened and 59 cases including 6 of our own were identified. The vast majority (78%) were female. Fifty patients (84.7%) presented in the newborn period. Half of the cases (52.5%) had associated anomalies and 13 neonates (22%) required oxygen supplementation including CPAP or ventilatory support before surgery. In 73% of the cases, a resection of gut was undertaken. Histopathological assessment in 44 cases (74.6%) revealed no ectopic gastric mucosa. Three cases demised prior to treatment. The outcome in the vast majority was excellent with 84.7% surviving and discharged well. Conclusion Perforated MD is an unusual cause of a pneumoperitoneum in the newborns. Diagnosis is established at laparotomy and it rare to find ectopic mucosa histopathologically. The overall outcome is excellent.